PECULIARITIES OF EXPRESSION OF TOURISM IN UZBEK AND FRENCH LANGUAGES (Proceedings of International Educators Conference, 2024)
Today, the development of tourism in the Republic of Uzbekistan is growing from year to year, due to the fact that in our article the tourism industry is one of the fastest growing. The use of terms entering this field from the point of view of this field forces them to be studied carefully. We will consider them on the example of Uzbek and French, as well as on the example of words with the word "tour" in the field of tourism.